Mekanisme Pasar, Konsep Harga, dan Kebijakan Moneter: Relevansi Isu Terkini dengan Pemikiran Ibnu Taimiyah - Baitulloh, Sabit; Yuliani; Mutafarida, Binti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The Islamic economic system that exists today has actually existed since the time of the Prophet Muhammad SAW. Along with the times came several thinkers and scholars who were critical of economic issues. One of them is Ibn Taymiyyah, he expressed many thoughts about economics, but in this scientific work the author wants to discuss three thoughts of Ibn Taymiyyah, namely the market mechanism, the concept of price, and monetary policy. This scientific work uses a qualitative method with a literature analysis approach in which this research examines events or history and past events that are accumulated and then analyzed. The results of this study prove that the three results of Ibn Taymiyyah's thought centuries ago are still relevant if applied to economic conditions today.